Developmental silencing of the AtTERT gene is associated with increased H3K27me3 loading and maintenance of its euchromatic environment - Ogrocká, Anna; Sýkorová, Eva; Fajkus, Jirí; Fojtová, Miloslava (Journal of experimental botany, 2012)
Telomerase, an enzyme responsible for the maintenance of linear chromosome ends, is precisely regulated during plant development. In animals, involvement of the epigenetic state of the telomerase reverse transcriptase (TERT) gene in the complex regulation of telomerase activity has been reported. To reveal whether epigenetic mechanisms participate in the regulation of plant telomerase, the relationship between telomerase activity in tissues of Arabidopsis thaliana and DNA methylation and histone modifications in the A. thaliana TERT (AtTERT) upstream region was studied. As expected, a gradual decrease of telomerase activity during leaf maturation was observed. A different pattern with a more progressive loss of telomerase activity and AtTERT transcription during leaf development was revealed in MET1 gene-knockout mutants. Analysis of DNA methylation in the AtTERT upstream region showed low levels of methylated cytosines without notable differences between telomerase-positive and telomerase-negative wild-type tissues. Surprisingly, a high level of CG methylation was found in the AtTERT coding region, although this type of methylation is a characteristic attribute of constitutively expressed genes. Analysis of chromatin modifications in the AtTERT upstream region and in exon 5 showed increased loading of the H3K27me3 mark in the telomerase-negative mature leaf compared to telomerase-positive seedlings, whereas H3K4me3, H3K9Ac, and H3K9me2 were approximately at the same level. Consistently, the chromatin structure of the AtTERT gene was maintained. These results are discussed in the context of the general involvement of epigenetic mechanisms in the regulation of gene expression and with respect to similar studies performed in animal models.
Keywords: metylace; Euchromatin; Arabidopsis Proteins; Telomerase; Gene Expression Regulation, Developmental; Up-Regulation; euchromatin; umlčování genů; Gene Silencing; telomerasa; upregulace; proteiny huseníčku; Methylation; epigeneze genetická; Exons; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; Arabidopsis; exony; histony; Histones; vývojová regulace genové exprese; Epigenesis, Genetic